Children`s Fine Motor Development Through Ecoprint Techniques On Totebag - Indah Wulandari; Sariah Sariah; Sakilah Sakilah; Indah Wati; Nurhayati Nurhayati; Arbi Arbi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This research aimed at finding out the effect of Ecoprint technique on Totebags toward fine motor development of 5-6 years old children at Islamic Kindergarten of Al-Muttaqin Pekanbaru City. Quantitative experiment method was used in this research with pre-experimental one group pretest posttest design. T-test was used with the formula that tobserved was higher than ttable. If tobserved was higher than ttable, H0 was rejected and Ha was accepted. The subjects were teachers and 5-6 years old children at Islamic Kindergarten of Al-Muttaqin. The object was the effect of Ecoprint technique on Totebags toward fine motor development of 5-6 years old children at Islamic Kindergarten of Al-Muttaqin. All children on group B2 at Islamic Kindergarten of Al-Muttaqin were the population of this research, and they were 18 children. Total sampling technique was used in this research. Observation and documentation were the techniques of collecting data. The techniques of analyzing data were validity test, reliability test, normality test, homogeneity test, and hypothesis test (t-test). SPSS 20 was used to analyze data. The result of statistical t-test showed that the score of sig. 0.001 was lower than 0.05, and tobserved 18.734 was higher than ttable 1.73961. So, H0 was rejected and Ha was accepted. It could be concluded that there was an effect of Ecoprint technique on Totebags toward fine motor development of 5-6 years old children at Islamic Kindergarten of Al-Muttaqin Pekanbaru City. Keywords: Ecoprint Technique on Totebags, Fine Motor, Early Childhood